2018
DOI: 10.1080/08995605.2017.1420980
|View full text |Cite
|
Sign up to set email alerts
|

Relation between coping and posttrauma cognitions on PTSD in a combat-trauma population

Abstract: Individual differences in cognitive processes and coping behaviors play a role in the development and maintenance of posttraumatic stress disorder (PTSD). Given the large numbers of combat-exposed service members returning from the Operation Enduring Freedom (OEF), Operation Iraqi Freedom (OIF), and Operation New Dawn (OND) conflicts, exploring individual differences in cognitive-affective processes is important for informing our understanding of PTSD etiology and early intervention in military samples. The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 56 publications
(74 reference statements)
2
9
1
Order By: Relevance
“…When controlling for negative cognitions on oneself and the world, self-blame was even associated with lower PTSD symptom severity. This replicates previous findings (e.g., Sheerin et al 2018;Startup et al 2007). One intriguing explanation for this could be the protective function of a feeling of control originating from behavioral self-blame (Koss et al 2002), which is part of the subscale measuring self-blame.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…When controlling for negative cognitions on oneself and the world, self-blame was even associated with lower PTSD symptom severity. This replicates previous findings (e.g., Sheerin et al 2018;Startup et al 2007). One intriguing explanation for this could be the protective function of a feeling of control originating from behavioral self-blame (Koss et al 2002), which is part of the subscale measuring self-blame.…”
Section: Discussionsupporting
confidence: 90%
“…Meanwhile, we should consider that these results may have been compromised by the low Crohnbach's alpha for the self-blame subscale, as outlined in previous work (e.g., Beck et al 2004;Müller et al 2010). As the current study is not the first to find a negative relation between self-blame and PTSD symptoms (e.g., Sheerin et al 2018;Startup et al 2007), it is important to study the role of selfblame for PTSD in more detail and make sure that instruments are adequate.…”
Section: Discussionmentioning
confidence: 98%
“…Combatants' inadequate response to extreme conditions using negative coping behaviors may be predictors of the development and maintenance of PTSD. This was also confirmed by Sheerin, Chowdhury, Lind et al (2018) who found that avoiding coping, but no other coping strategy, was significantly positively related to PTSD diagnosis in the initial step [13].…”
Section: Resultssupporting
confidence: 70%
“…That is, people’s inabilities to change their thoughts and adaptively respond to different situations are more strongly related to recent PTSD symptoms, whereas people’s inabilities to use a variety of regulatory strategies are more strongly related to increased lifetime PTSD symptoms. A possible explanation for these results is that recent PTSD symptoms may be more inversely related to global beliefs about oneself and one’s abilities (in line with a Cognitive Processing Therapy framework; Held et al, 2018 ; for a review, see, Zalta, 2015 ), while lifetime PTSD symptoms may be more inversely related to the ways in which a person could or has coped ( Rauch et al, 2013 ; Sheerin et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%